2017
DOI: 10.1093/intimm/dxx031
|View full text |Cite
|
Sign up to set email alerts
|

Hyperferritinemia and inflammation

Abstract: Understanding of ferritin biology has traditionally centered on its role in iron storage and homeostasis, with low ferritin levels indicative of deficiency and high levels indicative of primary or secondary hemochromatosis. However, further work has shown that iron, redox biology and inflammation are inexorably linked. During infection, increased ferritin levels represent an important host defense mechanism that deprives bacterial growth of iron and protects immune cell function. It may also be protective, lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
407
1
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 476 publications
(475 citation statements)
references
References 105 publications
7
407
1
10
Order By: Relevance
“…7 High ferritin levels can be triggered by a variety of clinical and pathophysiological mechanisms that are similar to HLH. 8 In our study, elevated ferritin levels (>1554 g/L) at 7 days after treatment of sepsis displayed considerable power for differentiating SAHS from sepsis. The cutoff value of ferritin was lower than the established level of 10 000 g/L.…”
Section: Reply To: Comment On: Cd163 As a Valuable Diagnostic And Promentioning
confidence: 49%
See 1 more Smart Citation
“…7 High ferritin levels can be triggered by a variety of clinical and pathophysiological mechanisms that are similar to HLH. 8 In our study, elevated ferritin levels (>1554 g/L) at 7 days after treatment of sepsis displayed considerable power for differentiating SAHS from sepsis. The cutoff value of ferritin was lower than the established level of 10 000 g/L.…”
Section: Reply To: Comment On: Cd163 As a Valuable Diagnostic And Promentioning
confidence: 49%
“…Otrock and colleagues proved that a serum ferritin level >10 000 μg/L is not specific for HLH in either 583 adult patients or 45 children . High ferritin levels can be triggered by a variety of clinical and pathophysiological mechanisms that are similar to HLH . In our study, elevated ferritin levels (>1554 μg/L) at 7 days after treatment of sepsis displayed considerable power for differentiating SAHS from sepsis.…”
mentioning
confidence: 45%
“…More importantly, during the course of the study, we also found how SF was an independent risk factor for NHLAIS. SF (an iron storage protein) is related to inflammation and closely linked to a hypercoagulable state in patients with cancer [25][26][27]. Although the detailed mechanism of SF in a hypercoagulable state remains unclear, we speculated that elevated SF may promote hypercoagulability due to severe inflammatory response, leading to ischemic stroke in NHL patients.…”
Section: Resultsmentioning
confidence: 98%
“…Ferritin is an iron storage protein influenced by the intracellular iron concentrations. It is also an acute‐phase protein, which is increased in the setting of inflammation, even exceeding 10 000 ng/mL in septic shock and infectious diseases with macrophage activation . Increased ferritin level is also observed in alcoholism, cytolysis (including hepatic and muscle cytolysis), metabolic syndrome, juvenile idiopathic arthritis, and adult‐onset Still's disease .…”
Section: Introductionmentioning
confidence: 99%
“…activation. [7][8][9] Increased ferritin level is also observed in alcoholism, cytolysis (including hepatic and muscle cytolysis), metabolic syndrome, juvenile idiopathic arthritis, and adult-onset Still's disease. [10][11][12] One study revealed that ferritin could be a useful early prognostic factor in DRESS.…”
mentioning
confidence: 99%